Experimental Study on Rheological Properties of Thinkened Co2 in Liquid and Supercritical State. (17th November 2018) - Li, Binfei; Shi, Dashan; Lv, Qichao; Bai, Hao; Zheng, Chao; Xu, Jianguo
Abstract: The rheology of CO2 fracturing fluid are complicated because of its phase change. In this work, pipeline rheology of CO2 in a range of 8–16 MPa and 10–60 °C were studied. The results showed that the thickened CO2 was characterized by a power-law fluid. With the thickener or pressure increased, the consistency coefficient K increased and the flow index n decreased. In the liquid or supercritical state, temperature increasing made the K decrease and the n increase. However, when CO2 transformed from the liquid to the supercritical state in 30–40 °C, and the K increased while the n decreased.